Could protein phosphatase 2A and glycogen synthase kinase-3 beta be targeted by natural compounds to ameliorate Alzheimer’s pathologies? - Manoharan, Sushmitaa Dhevii; Abdul Hamid, Hafizah; Md Hashim, Nur Fariesha; Cheema, Manraj Singh; Musa Chiroma, Samaila; Mustapha, Muzaimi; Mehat, Muhammad Zulfadli (Elsevier, 2024)
Alzheimer’s disease (AD) is a progressive neurological disorder that impairs memory and cognitive abilities, primarily in the elderly. The burden of AD extends beyond patients, impacting families and caregivers due to the patients’ reliance on assistance for daily tasks. The main features of the pathogenesis of AD are beta-amyloid plaques and neurofibrillary tangles (NFTs), that strongly correlate with oxidative stress and inflammation. NFTs result from misfolded and hyperphosphorylated tau proteins. Various studies have focused on tau phosphorylation, indicating protein phosphatase 2A (PP2A) as the primary tau phosphatase and glycogen synthase kinase-3 beta (GSK-3β) as the leading tau kinase. Experimental evidence suggests that inhibition of PP2A and increased GSK-3β activity contribute to neuroinflammation, oxidative stress, and cognitive impairment. Hence, targeting PP2A and GSK-3β with pharmacological approaches shows promise in treating AD. The use of natural compounds in the drug development for AD have been extensively studied for their antioxidant, antiinflammatory, anti-cholinesterase, and neuroprotective properties, demonstrating therapeutic advantages in neurological diseases. Alongside the development of PP2A activator and GSK-3β inhibitor drugs, natural compounds are likely to have neuroprotective effects by increasing PP2A activity and decreasing GSK-3β levels. Therefore, based on the preclinical and clinical studies, the potential of PP2A and GSK-3β as therapeutic targets of natural compounds are highlighted in this review.